DISCURSUS OF MANAGEMENT OF TAMAN AYUN TEMPLE AFTER UNESCO DETERMINED AS A PART OF WORLD CULTURAL HERITAGE - Sandijaya, Maulana (E-Journal of Cultural Studies; Volume 12, Number 3, August 2019, 2019)
UNESCO made a movement to establish Taman Ayun temple as world culture heritage in 2012. Puri Ageng Mengwi as the owner of Taman Ayun temple considered revitalization of Taman Ayun is the way to preserve cultural heritage. The revitalization is also for beautifying Taman Ayun temple in order to give pleasure for visitors, it continuing from 2013 until 2016. However, the revitalization emerged many pro and con between Mengwi and Gulingan villages, part of society felt ignored and disturbed. For example, the “pekaseh”, Puri Mayun Wed and Kaleran, merchants in Tenten market, and Badung Goverment. Theoriticaly, Taman Ayun Temple as world culture heritage should give advantages for society surrounding, but in this case, farmer’s members of Subak Beringkit and Bukti Batan badung did not get any compensation from UNESCO and Taman Ayun. The condition showed up many difference point of view, each sides conveyed their opinions and strongly defend their thoughts. This condition was very interesting to study the form of discourse, ideology behind discourse and implication of diskursus in reality. The researcher got all of those diskursus from interview, observation, and newspaper. This research used qualitative method by collecting data through observation, interview and documentation from newspaper. Data analyzed using hegemony theory, relasi kuasa theory, and kuasa pengetahuan theory. Those three theories as the base in researching to uncover the problems in diskursus. The result of the reasearch pointed out the differences of ideology behind diskursus management of Taman Ayun temple after UNESCO establish it as one of world culture heritage.  Keywords: manufacture, diskursus, Taman Ayun temple, world cultural heritage .